2009
DOI: 10.1001/archinternmed.2009.70
|View full text |Cite
|
Sign up to set email alerts
|

Career Fit and Burnout Among Academic Faculty

Abstract: The extent to which faculty physicians are able to focus on the aspect of work that is most meaningful to them has a strong inverse relationship to their risk of burnout. Efforts to optimize career fit may promote physician satisfaction and help to reduce attrition among academic faculty physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
388
3
16

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(416 citation statements)
references
References 26 publications
9
388
3
16
Order By: Relevance
“…Many issues have previously been identified that affect primary care clinicians, among them the electronic health record, 11,12 inefficiencies in office practice, lack of teamwork, time pressure during office visits, 6 a lack of control in the workplace, 6 and a lack of career fit for time to do what one is most passionate about. 20 Clinics serving minority patients have especially challenging work conditions, 21 and primary care may be hardest to support where it is needed most.…”
Section: Discussionmentioning
confidence: 99%
“…Many issues have previously been identified that affect primary care clinicians, among them the electronic health record, 11,12 inefficiencies in office practice, lack of teamwork, time pressure during office visits, 6 a lack of control in the workplace, 6 and a lack of career fit for time to do what one is most passionate about. 20 Clinics serving minority patients have especially challenging work conditions, 21 and primary care may be hardest to support where it is needed most.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout is linked with significant personal distress, including depression, substance abuse, divorce, 30,31 and plans to leave the medical profession, 32 all outcomes that are relevant to the affected physician. What our study's results may suggest is that, from the patient perspective, burned-out residents are not Bbad^doctors.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Academic physicians are especially at high risk for experiencing stress because of multiple demands and expectations. 8 Negative effects of physician distress include decreasing level of satisfaction, attrition from academic practice, loss of empathy, decrease in idealism, poor mental health, and burnout. 7,9 Burnout may affect an estimated 25-60% of physicians.…”
Section: Introductionmentioning
confidence: 99%